Non-destructive testing of a Zr–1Nb zirconium alloy with a protective Cr/Mo thin layers coating for the production components of corrosion-resistant for nuclear reactors; Перспективные материалы конструкционного и функционального назначения - Salman A. M. (Модификация поверхности, 2024)
The study explores the effectiveness of Cr- and Cr/Mo-coated Zr-1Nb zirconium alloys. The coatings, deposited through magnetron sputtering, provided protection during high-temperature oxidation. The Mo sublayer prevented Cr-Zr interdiffusion. The study used various NDT methods to evaluate the structural soundness and effectiveness of Cr/Mo coatings. Results showed that Cr/Mo coatings significantly enhance the long-lastingness and dependability of zirconium alloy components in emergency situations